Tradisi Sholawat Mansub Habib Sholeh Bin Muhsin Al-Hamid di Tempeh Tengah, Lumajang - Rizqotul Luqi Mufidah; Norma Azmi Farida (Jurnal Living Hadis, 2020)
Living Quran and Hadith studies are increasingly prevalent in Indonesia, the studies increasingly reveals that many traditions of society or groups are based on the Qur’an and hadith. This article focuses on the tradition of reading the sholawat mansub by Habib Sholeh bin Muhsin Al-Hamid in Tempeh Tengah Village, Tempeh District, Lumajang Regency, East Java. Shalawat mansub is a result of the spiritual journey of Habib Sholeh who met with the Prophet Khidir.Then it become a community tradition that was read every night Friday Kliwon 141 times. Then the community perpetuates the recitation of sholawat mansub  as a means of tawasul to facilitate all matters. This paper aims to identify phenomenon that use Talal Asad’s theory that Islam as a discursive tradition. This research is a field research about the phenomenon of living hadith. The data used are library sources and interviews that are processed in analytic descriptive. The result of this study are the tradition of reading the blessings of Mansub as a discursive tradition that is accepted and practiced by the people of Central Tempeh, Lumajang. So that the hadiths related to this phenomenon are presentedas a form of text that intermediate human's approach to Allah Swt.